Initial-Condition-Aware Polynomial Guidance with Impact Time and Angle Constraints - Duan, Xinyao; Wang, Jiang; Wang, Yadong; Fan, Shipeng (Aerospace, 2025)
With the growing application demands for cooperative guidance systems, the ITAC guidance law has undergone rapid technological advancement in recent research developments. However, existing ITAC methods often overlook the critical issue of command discontinuity during the midcourse-to-terminal guidance handover stage. To address this gap, this study proposes a novel fifth-order polynomial guidance law that simultaneously incorporates initial conditions (flight path angle and acceleration) and ensures precise ITAC performance. The method analytically derives polynomial coefficients from boundary constraints and transforms them into a computationally efficient closed-loop guidance law. Additionally, a positional error compensation term is derived to enable the practical realization of the proposed guidance law. Numerical simulations demonstrate the advantages of the proposed guidance law compared to existing methods. The results confirm that the fifth-order polynomial guidance law effectively resolves midcourse-terminal handover challenges while maintaining computational efficiency, offering a viable solution for cooperative guidance systems that require ITAC capability.